Comparative Analysis of CODAS, TOPSIS, and COCOSO Methods Using Objective Weighting in Multi-Criteria Decision Support Systems - Setiawansyah Setiawansyah; Very Hendra Saputra; Agung Deni Wahyudi (PT. SNN MEDIA TECH PRESS, 2026)
This study aims to objectively assess teachers' pedagogical performance through the application and comparison of three multi-criteria decision-making methods, namely CODAS, TOPSIS, and COCOSO, with the criteria weights determined using the ITARA method. The ranking results show differences in evaluation patterns among the methods, where the CODAS method places Teacher RD in the first rank, followed by Teacher GH and Teacher DG, while Teacher AN is ranked last. In contrast, the TOPSIS and COCOSO methods produced relatively consistent rankings, with Teacher TY ranking first, followed by Teacher AN and Teacher NH in TOPSIS, and Teacher NH and Teacher DG in COCOSO. These differences in results indicate that each method has a different evaluative perspective on the performance of alternatives, depending on the preference calculation approach used. Overall, this comparative analysis confirms that using more than one ranking method can provide a more comprehensive and balanced view in evaluating teachers' pedagogical performance, thereby supporting more accurate and data-driven decision-making.